The ω-carboxyl group of 7-ketocholesteryl-9-carboxynonanoate mediates the binding of oxLDL to CD36 receptor and enhances caveolin-1 expression in macrophages. (September 2017) - Li, Jingda; Yu, Chengjie; Wang, Renjun; Xu, Jianrong; Chi, Yan; Qin, Jianzhong; Liu, Qingping
Abstract: CD36 signal transduction modulates the uptake of oxidized low-density lipoprotein (oxLDL) and foam cell formation. We previously observed that 7-ketocholesteryl-9-carboxynonanoate (oxLig-1), the lipid moiety of oxLDL, activates the CD36-Src-JNK/ERK1/2 signalling pathway. In this study, we assessed the role of the ω-carboxyl group in the binding of oxLig-1 to CD36 and investigated whether the binding of the ω-carboxyl group to CD36 triggers CD36-mediated signalling, thereby resulting in the upregulation of caveolin-1 expression. Our results showed that oxLig-1 bound to CD36 and that the ω-carboxyl group was critical for this binding. Furthermore, immunoprecipitation and Western blot analyses showed that interaction between the ω-carboxyl group of oxLig-1 and CD36 triggered intracellular Src-JNK/ERK1/2 signal transduction. Moreover, the binding of the ω-carboxyl group to CD36 induced caveolin-1 expression and translocation to the membrane in macrophages. Additionally, inhibitors of Src, JNK and ERK and siRNA targeting CD36 and NF-κB significantly suppressed the enhanced caveolin-1 expression induced by oxLig-1. In conclusion, these observations suggest that oxLig-1 is a critical epitope of oxLDL that mediates the binding of oxLDL to CD36 and activates downstream Src-JNK/ERK1/2-NF-κB signal transduction, resulting in upregulation of caveolin-1 expression in macrophages.